1999
DOI: 10.1046/j.1365-2893.1999.00155.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B and C markers in volunteer blood donors in Crete. A 5‐year study

Abstract: Greece is a country with an intermediate prevalence of hepatitis B virus (HBV) and hepatitis C virus (HCV) infection. Crete, the third-largest island of the Mediterranean sea, has a different prevalence of viral hepatitis. One-eighth of the total island population, of 550,000, was included in a 5-year study of blood donors from three out of four blood banks, serving three out of four prefectures of the island. Markers for HBV and HCV were studied and evaluated according to geographical area, gender and age of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
18
2
12

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 14 publications
9
18
2
12
Order By: Relevance
“…Of the HBV-infected population, nineteen (86.4%) were males and 3(13.6%) were females with mean age of 39.7 ±16.3yrs and 35.3±9.7yrs respectively. The results of this study is concordance with two recent large series study from Greece and New Zealand and another by Pei-Kwei and his coresearchers which showed a higher HBsAg prevalence in males than females [33][34][35]. However, this is in contrast to the findings in Taiwan patients where HBsAg prevalence between genders was not significantly different in in a Resource-Limited Setting epidemiologic studies in Taiwan [36][37][38].…”
Section: Discussionsupporting
confidence: 91%
“…Of the HBV-infected population, nineteen (86.4%) were males and 3(13.6%) were females with mean age of 39.7 ±16.3yrs and 35.3±9.7yrs respectively. The results of this study is concordance with two recent large series study from Greece and New Zealand and another by Pei-Kwei and his coresearchers which showed a higher HBsAg prevalence in males than females [33][34][35]. However, this is in contrast to the findings in Taiwan patients where HBsAg prevalence between genders was not significantly different in in a Resource-Limited Setting epidemiologic studies in Taiwan [36][37][38].…”
Section: Discussionsupporting
confidence: 91%
“…The peak exposure rates for both males (36.17%) and females (27.38%) detected in the 41–60 years age groups are much higher than the ones reported for blood donors (between 8% and 9.5% in different prefectures) and probably are due to the fact that in general, blood donors are younger than hospitalized patients. When blood donors of over 40 years of age are considered, the exposure rates are similar (23.32%) [8]. …”
Section: Resultsmentioning
confidence: 99%
“…Clinical studies have emphasized many differences between the island and mainland Greece, in both liver cell carcinoma characteristics and prevalence of viral markers [6]. A recent study in blood donors in northwest Greece reported an HBsAg prevalence of 0.85% [7] while a study of blood donors in Crete has shown a significantly lower prevalence of 0.40% for the same viral marker [8]. A survey of blood donors in mainland Greece reported a 0.4% prevalence of anti-HCV using a second generation enzyme linked immuno-assay (ELISA 2) [9] not different from the overall prevalence found with the same screening test in Crete (0.38%), but with marked differences among the prefectures of the island (Heraklion 0.52%, Rethymnon 0.52%, Chania 0.23%) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the rate of anti-HCV among blood donors in Sudan was 0.65% [19] and 0.3% among blood donors from the National Blood Transfusion Center in Baghdad, Iraq, from 2006-2009 [25]. In Crete, the prevalence of anti-HCV in donors was 0.49% in females and 0.37% in males [26]. On the other hand, the seroprevalence rate of anti-HCV positive individuals in Israel was reported to be 1.96% in 2001-2010, while the infection rate reached more than 4% among immigrants from the former USSR [27].…”
Section: Discussionmentioning
confidence: 99%